Digital literacy through gaming: A comparative study of knowledge acquisition, social presence, and emotional reactions in digital and non-digital board games - Pakinee Ariya; Natchaya Wongwan; Kannikar Intawong; Kitti Puritat (Social Sciences and Humanities Open)
The trend of educational board games is experiencing significant growth, with notable integration of technology; however, many educators continue to use both digital and physical board games. Digital board games offer convenience, accessibility, and enhanced interactivity through features like animations, sound effects, and automated rule enforcement. In contrast, physical board games emphasize tactile engagement and face-to-face social presence, fostering a stronger sense of connection among players. This study investigates the comparative impacts of digital and non-digital board games on knowledge acquisition, social presence, and emotional reactions among higher education students. Employing a quasi-experimental design, 82 students enrolled in an Information Literacy course were divided into two groups: one using digital board games and the other using non-digital board games. Pre- and post-tests measured knowledge acquisition, while the Social Presence in Gaming Questionnaire (SPGQ) and the Positive and Negative Affect Schedule (PANAS) assessed social and emotional impacts. Results indicate that both digital and non-digital games significantly enhance knowledge acquisition, with no substantial differences between the two formats. However, digital board games showed higher engagement levels, suggesting a greater potential for promoting active participation. Emotional responses were similar across both groups, with no significant differences in positive or negative affect. These findings underscore the educational value of both game formats and highlight the importance of selecting the appropriate type based on specific educational objectives.